Pengendalian Kualitas Metode Six Sigma Untuk Mengurangi Tingkat Kerusakan Produk Kalender Di PT. KLM - Agustian Waruwu; Vivian Rensi Tampubolon; Muhammad Agung Pratama; Destiana Putri (LPPM Universitas Bina Sarana Informatika, 2022)
Every company must be able to compete to improve the quality of products and services provided to consumers. Companies are competing to do many product innovations and improve quality and reduce product defects (reject) so that companies can achieve the expected benefits or profits. Likewise with the company PT. KLM, which is engaged in calendar printing, of course wants to produce quality products so that it can compete with other businessmen. In producing the calendar product, there are obstacles or problems encountered related to product defects. Based on the processed data, it can be explained that the total level of disability that occurs at PT. KLM by reaching 12.8%. To find out the causes of product defects in calendar design, a production quality control method is used, one of which is the Six Sigma method. Six Sigma is a quality control tool that can be used to measure the level of defects in service or manufacturing industries. In the application of six sigma using the DMAIC approach. From the results of the study, it was shown that the most potential causes in producing the final product were identified as follows: the type of defect in italics was 1343, then the number of blurry colors was 2856, then the number of images cut off was 870. From the calculation results of PT. KLM has a sigma level of 3.1 > 3.2 with the possibility of damage to the production of 41,000 calendars when producing 1,000,000 calendars.